The application of clinical genetics: editorial - Maurer, Martin H. (The application of clinical genetics, 2012)
The Application of Clinical Genetics Martin H MaurerDepartment of Physiology and Pathophysiology, University of Heidelberg, Heidelberg, Germany; Mariaberg Hospital for Child and Adolescent Psychiatry, Gammertingen, GermanyIn 2012, The Application of Clinical Genetics enters its fifth year of publication. The journal has had a change of Editor-in-Chief: Dr David H Tegay stepped down and I was appointed to serve as the new Editor-in-Chief. As his successor, I thank Dr Tegay for his great work for the journal. I hope I can continue his successful editorial contributions. Moreover, I thank the many reviewers for their sustained support of the journal.The Application of Clinical Genetics is dedicated to open access publishing – as all Dove Press journals are. This means that authors will be charged for the publication process, but the acceptance of a manuscript is based solely on its scientific quality. This is what I will be responsible for as Editor-in-Chief. The team at Dove Press is a constant help with all administrative duties concerning peer reviewal, and I want to express my thanks for their prompt and reliable help. The field of clinical genetics is facing new challenges with the broad availability of large-scale screening methods for gene mutations, such as high-throughput sequencing and biochips. This means that ethical issues regarding the handling of genetic information must be addressed, both for the individual and for society.1–3 For example, sequencing of cell-free, fetal nucleic acids in the maternal blood to locate fetal aneuploidy, especially trisomy 21, may become broadly available soon, with even faster results than conventional methods such as amniocentesis.